2015
DOI: 10.1007/s12104-015-9596-0
|View full text |Cite
|
Sign up to set email alerts
|

Chemical shift perturbations induced by residue specific mutations of CaM interacting with NOS peptides

Abstract: The regulation of Nitric oxide synthase (NOS) by calmodulin (CaM) plays a major role in a number of key physiological and pathological processes. A detailed molecular level picture of how this regulation is achieved is critical for drug development and for our understanding of protein regulation in general.CaM is a small acidic calcium binding protein and is required to fully activate NOS. The exact mechanism of how CaM activates NOS is not fully understood at this time. Studies have shown CaM to act like a sw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 11 publications
(10 reference statements)
1
0
0
Order By: Relevance
“…15 N-labeled CaM was titrated with the ubiquitin-hENT1 loop construct, and the limited amount of line broadening confirmed that the hENT1 loop binds to CaM (Fig. 4A) in the presence of calcium, similar to other studies that have examined the interaction of a protein domain with CaM (44).…”
Section: C812supporting
confidence: 81%
“…15 N-labeled CaM was titrated with the ubiquitin-hENT1 loop construct, and the limited amount of line broadening confirmed that the hENT1 loop binds to CaM (Fig. 4A) in the presence of calcium, similar to other studies that have examined the interaction of a protein domain with CaM (44).…”
Section: C812supporting
confidence: 81%